Natural convection and fluid flow in inclined enclosure with a corner heater - Varol, Yasin; Öztop, Hakan Fehmi; Koca, Ahmet; Ozgen, Filiz (Pergamon-Elsevier Science Ltd, 2009)
The phenomena of natural convection in an inclined square enclosure heated via corner heater have been studied numerically. Finite difference method is used for solving momentum and energy equations in the form of stream function-vorticity. One wall of the enclosure is isothermal but its temperature is colder than that of heaters while the remaining walls are adiabatic. The numerical procedure adopted in this analysis yields consistent performance over a wide range of parameters; Rayleigh number, Ra (10(3) <= Ra <= 10(6)): Prandtl number, Pr (0.07 <= Pr <= 70); dimensionless lengths of heater in x and y directions (0.25 <= hx <= 0.75. 0.25 <= hy <= 0.75); and inclination angle, phi (0 degrees <= phi <= 270 degrees). It is observed that heat transfer is maximum or minimum depending on the inclination angle and depending on the length of the corner heaters. The effect of Prandtl number on mean Nusselt number is more significant for Pr < 1. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Corner heaters; Natural convection; Inclined; Enclosure